Smart City Management based on IoT - Florin NEMÈšANU; Florina PÃŽNZARU (Smart Cities and Regional Development Journal)
The smart city concept is now a target for the development of urban areas. The urban challenges (pollution, overpopulation, resources etc.) are pressuring on urban governance and the municipalities have to find solutions for all these issues as well as a new way to develop the city. Technological progress in ICT as well as the facile access to these technologies could be a good reason to open the city for the smart city approach. Internet of things could be a technological solution in terms of finding the optimum way in making the decision on urban life. A smart city management based on IoT could solve the problem of collecting information from the urban area, processing information and making the right/optimum decision for city management.